Fight academic apartheid to advance equality and quality in the sciences! Europe’s Open Access Champions - Proudman, Vanessa (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. “Fight academic apartheid to advance equality and quality in the sciences!” “Stop discriminating against Open Access publications in research evaluation.” “The next generation of researchers will care less about status and more about relevance.” These are some of the voices from Europe’s rectors, vice-chancellors, professors, senior and junior researchers on what still needs to be done to achieve more Open Access. Despite seeing significant international and national Open Access policy development across Europe, both the library and academic communities are still having challenges in implementing Open Access policies on various levels. We can anticipate far more OA take-up when the research community and senior administration votes with their feet against traditional publishing practices and for new forms. In addition, these groups have the power to stabilise and strengthen the sustainability of such change by changing the way that research is currently being assessed and evaluated. It is for this reason that SPARC Europe is highlighting the importance of the people in our research communities who are helping make Open Access happen and who are speaking out for such change. SPARC Europe is doing this by bringing champions together in an online showcase, Europe’s Open Access Champions. This features a range of academics and senior administrators or champions who are making the case for Open Access amongst their peers. They are generating more momentum for more access to Europe’s research results within their research communities. They tell us why and how – in their own words – on the Europe’s Open Access Champions site. In the first instance, this presentation will share a range of complementary but also very different views from champions from various research roles, disciplines and countries. What needs to be done to change the current scholarly publishing system in their view? Where does academic integrity come in and how can more OA here potentially affect research careers / employment conditions? Above all, how can the academic community make the necessary change to the way research is currently assessed and evaluated to make OA work? The presentation will then go on to share lessons learnt by various libraries across Europe on what makes a good OA champion. To conclude, this presentation seeks to inspire the open scholarly communication community to engage more with champions from the research community who have the potential to make more rapid Open Access to Europe’s research results.